2006
DOI: 10.1093/toxsci/kfj153
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and Nuclear DNA Damage Induced by Curcumin in Human Hepatoma G2 Cells

Abstract: Curcumin is extensively used as a spice and pigment and has anticarcinogenic effects that could be linked to its antioxidant properties. However, some studies suggest that this natural compound possesses both pro- and antioxidative effects. In this study, we found that curcumin induced DNA damage to both the mitochondrial and nuclear genomes in human hepatoma G2 cells. Using quantitative polymerase chain reaction and immunocytochemistry staining of 8-hydroxydeoxyguanosine, we demonstrated that curcumin induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(129 citation statements)
references
References 33 publications
10
107
0
2
Order By: Relevance
“…The induction of DNA damage that we observed in HEp-2 and 7T cells following the treatment with curcumin is in agreement with those previously reported, despite differences in the type of cells and experimental conditions used (Cao et al, 2006;Huang et al, 2011;Jiang et al, 2010;Lin et al, 2008;Lopez-Lazaro et al, 2007;Su et al, 2006;Urbina-Cano et al, 2006). Although we have expected that more oxidative DNA damage (like oxidized purines) would appear in HEp-2 and 7T cells because of ROS induction, strand breaks were predominant and correlated with cytotoxicity.…”
Section: Discussionsupporting
confidence: 93%
“…The induction of DNA damage that we observed in HEp-2 and 7T cells following the treatment with curcumin is in agreement with those previously reported, despite differences in the type of cells and experimental conditions used (Cao et al, 2006;Huang et al, 2011;Jiang et al, 2010;Lin et al, 2008;Lopez-Lazaro et al, 2007;Su et al, 2006;Urbina-Cano et al, 2006). Although we have expected that more oxidative DNA damage (like oxidized purines) would appear in HEp-2 and 7T cells because of ROS induction, strand breaks were predominant and correlated with cytotoxicity.…”
Section: Discussionsupporting
confidence: 93%
“…[22][23][24][25][26][27][28][29][30] For instance, curcumin concentrations of 2.5 and 5 lg mL À1 were shown to induce DNA damage to both the mitochondrial and nuclear genomes in cells. 28 These reports raise concern about curcumin safety, as the induction of DNA alterations is a common event in carcinogenesis.…”
Section: Dear Editormentioning
confidence: 99%
“…40,[44][45][46][47][48] Experimental studies have demonstrated that, although low concentrations of curcumin induce antioxidant effects, higher concentrations of this compound increase the cellular levels of ROS. 4,9,23,28,[49][50][51][52][53] The presence of 2 a,b-unsaturated ketones in the chemical structure of curcumin may also mediate some of its negative properties. These chemical groups are known to react covalently with exposed thiol groups of cysteine residues of proteins through a reaction termed Michael addition.…”
Section: Dear Editormentioning
confidence: 99%
“…Moreover, the damage of lysosomal and mitochondrial by hydrogen peroxide was also prevented by 6-gingerol. By contrast, there is an increasing body of evidence to suggest the prooxidative effects of phytochemicals (Kelly et al, 2001;Cao et al, 2006). In our previous study, 6-gingerol can apparently act as a prooxidant.…”
Section: Rosmentioning
confidence: 63%